The Sensory Studies Manifesto Tracking the Sensorial Revolution in the Arts and Human Sciences - Howes, David 1957- (University of Toronto Press, 2022)
The Sensory Studies Manifesto explores the origin and development of the revolutionary new field of sensory studies.
Description based on publisher supplied metadata and other sources
Keywords: Kunstwissenschaft; Humanwissenschaften; Sinne; Electronic books